HUBUNGAN PERIODE LAKTASI, BCS DAN LINGKAR DADA DENGAN PRODUKSI SUSU SAPI PERAH FH (FRIESIAN HOLSTEIN) DI KPSP SETIAKAWAN KABUPATEN PASURUAN - Andhari, Gabriella Intan; Surjowardojo, Puguh; Rifa'i, Rifa'i (Bantara Journal of Animal Science, 2023)
The purpose of this research was to determine the relationship between lactation period, BCS and chest circumference with milk production of Friesian Holstein dairy cattle. The material used 36 dairy cattles period 3, 4, and 5. This research has conducted in farm KPSP Setia Kawan, Nongkojajar, Pasuruan on 20 July - 20 October 2022. The method used in this research was case study. The data collection technique in this study was purposive sampling. The variables observed were period lactation, BCS, chest circumference and milk production. Data obtained were analyzed by using correlation analysis, and simple linear regression analysis. The result showing that the linier regression equation between lactation period and milk production shows Y= 43.82 – 4.72X1 with a correlation coefficient negative is 0.65 and for the coefficient of determination is 42.3%, the meaning that for every increase 1 time of the lactation period, milk production will decrease 4.72 liters. The linier regression equation between BCS and milk production shows Y= 4.06 + 8.35X2 with a correlation coefficient positive is 0.70 and the coefficient of determination is 49.7%, the meaning is BCS that for every increase 1 score of the BCS, milk production will incrase 8.35 liters. The linier regression equation between chest circumference with milk production shows Y= (-17.57) + 0.22X3 with a correlation coefficient positive is 0.52 and the coefficient of determination is 27.3%, the meaning that for every increase 1 cm of the chest circumference, milk production will decrease 0.22 liters. It can be concluded that the more highly lactation period, milk production will decrease. Then the more highly score BCS and chest circumference, milk production will following high to.